MICROBIOLOGICAL CHARACTERISTIC OF INTESTINAL MICROFLORA IN CHILDREN WITH ALLERGIC DISEASES - ZH. V. Veselova; L. S. Kozlova; YU. P. Dzhioev; E. I. Ivanova; S. M. Popkova (Acta Biomedica Scientifica, 2012)
The results of bacteriological research of scatological material from children with allergic diseases (atopic dermatitis, bronchia! asthma combined, with allergic rhinitis, dermal and respiratory syndrome, allergic rhinitis) in Irkutsk are presented, in the article. 62 patients from 1 year to 17 years were examined, and. significant deviations from the scatological norm, were revealed: in lactic acid, bacteria — 75,8 % while the number of bifidobacteria was reduced, in 58 % of patients. The most frequently identified, bacteria were S. aureus (24,2 %) and. K. pneumoniae (14,5 %).